Metode Diskusi Kelompok Tipe Jigsaw dalam Keterampilan Berbicara Bahasa Jerman - Kiki Fikhiyatul Hidayah; Laelah Azizah (Universitas Negeri Makassar, 2023)
Abstract. This research is a class action research that consisted of two cycles. The aim of this research is to know the planning, process and learning outcomes of Jigsaw Type Discussion Method of German speaking skills of students XI MIPA I SMA Negeri 1 Polewali. The data of the research are quantitative and qualitative. The quantitative data were obtained through speaking skills tests in Cycle I and Cycle II and the qualitative data were obtained through observation and analyzed through the percentage technique. The results showed that speaking skills were 64.19% in the first cycle and 77.96% in the second cycle. This means that the Jigsaw Type group discussion method for German speaking skills can increase students' XI MIPA 1 SMA Negeri 1 Polewali.Keyword: Jigsaw Type, speaking skills, German